Can the First Fasting Plasma Glucose Test in Pregnancy Predict Subsequent Gestational Complications?. (11th April 2022) - Burlina, Silvia; Dalfrà, Maria Grazia; Belloni, Pietro; Ottanelli, Serena; Mecacci, Federico; Mello, Giorgio; Lapolla, Annunziata
Abstract : Objective . To determine the best cut-off level of pregnant women's first fasting plasma glucose (FFPG) test results for the prediction of subsequent onset of gestational diabetes mellitus (GDM) and to examine the association between FFPG and maternal and neonatal outcomes in a large Caucasian population. Methods . 1437 medical records of women with singleton pregnancies followed up between 2015 and 2018 were retrospectively analyzed. Data on FFPG tested in the first trimester and 75 g oral glucose tolerance test (OGTT) findings performed according to IADPSG criteria and Italian guidelines were collected and evaluated. The women's clinical and metabolic characteristics (age, prepregnancy body mass index (BMI), previous pregnancies complicated by GDM, timing of delivery, and gestational hypertension) were also recorded. The fetal variables considered were being large for gestational age (LGA) or small for gestational age (SGA), macrosomia, and hypoglycemia. Results . Among the 1437 pregnant women studied, 684 had a normal glucose tolerance (NGT) and 753 developed GDM. In a univariate analysis FFPG ≥92 mg/dl predicts the risk of GDM with an OR = 2.36 (95% CI 1.930–3.186; p < 0.001 ). In multivariate analysis, after adjusting for principal risk factors of GDM (BMI, previous GDM, age >35 years, family history of diabetes) FFPG ≥92 mg/dl was associated with the risk of GDM (OR = 1.92; 95% CI 1.488–2.492; p < 0.001 ). In univariate analysis, FFPG ≥92 mg/dl predict the risk of insulin therapy in GDM women with a OR = 1.88 (95% CI 1.230–2.066; p < 0.001 ). As regards LGA, in a multivariate analysis, after adjusting for BMI, FFPG ≥92 mg/dl was associated with the risk of LGA only in NGT women (OR = 2.34; 95% CI 1.173–4.574; p = 0.014 ), but not in GDM women. FFPG was not associated with other maternal or neonatal outcomes. Conclusions . FFPG ≥92 mg/dl is related to GDM diagnosis and to the need of insulin therapy if GDM is diagnosed. An early diagnosis and a prompt start of insulin therapy are essential to prevent maternal and fetal complications.